(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article examines the legal forms and functions of corporate integrity of a civil servant as a key element in ensuring the efficiency, transparency, and accountability of public administration. The main aspects of integrity are analyzed, including its role in preventing corruption, protecting public interests, enhancing the efficiency of public service, fostering a culture of ethical behavior, and preventing conflicts of interest. A review of the regulatory and legal mechanisms for ensuring the integrity of civil servants has been conducted, particularly focusing on the laws of Ukraine "On Civil Service" and "On Prevention of Corruption," as well as the activities of the National Agency on Corruption Prevention (NACP). Special attention is given to practical mechanisms for ensuring integrity, including asset and income declaration, implementation of anti-corruption programs, professional development of civil servants, and mechanisms of public oversight. The study identifies key challenges in ensuring integrity within public administration, including the legal ambiguity of certain aspects, the insufficient effectiveness of anti-corruption measures, political influence on oversight bodies, and the low level of ethical culture among officials. As a result of the research, a comprehensive approach is proposed to improve mechanisms for ensuring integrity, which includes legislative modernization, strengthening anti-corruption control, fostering an ethical culture among civil servants, and enhancing engagement with civil society. The implementation of these measures will contribute to increasing transparency, accountability, and public trust in government institutions.